Forebrain-selective AMPA-receptor antagonism guided by TARP γ-8 as an antiepileptic mechanism - Kato, Akihiko S; Burris, Kevin D; Gardinier, Kevin M; Gernert, Douglas L; Porter, Warren J; Reel, Jon; Ding, Chunjin; Tu, Yuan; Schober, Douglas A; Lee, Matthew R; Heinz, Beverly A; Fitch, Thomas E; et al. (Nature medicine, 2016)
Selective pharmacological blockade of forebrain excitatory AMPA receptors that express the TARP γ-8 subunit enables antiepileptic therapy in rodent models of epilepsy without inducing motor impairments associated with currently used antiepileptic drugs. Pharmacological manipulation of specific neural circuits to optimize therapeutic index is an unrealized goal in neurology and psychiatry. AMPA receptors are important for excitatory synaptic transmission 1 , and their antagonists are antiepileptic 2 . Although efficacious, AMPA-receptor antagonists, including perampanel (Fycompa), the only approved antagonist for epilepsy, induce dizziness and motor impairment 3 , 4 . We hypothesized that blockade of forebrain AMPA receptors without blocking cerebellar AMPA receptors would be antiepileptic and devoid of motor impairment. Taking advantage of an AMPA receptor auxiliary protein, TARP γ-8, which is selectively expressed in the forebrain and modulates the pharmacological properties of AMPA receptors 5 , we discovered that LY3130481 selectively antagonized recombinant and native AMPA receptors containing γ-8, but not γ-2 (cerebellum) or other TARP members. Two amino acid residues unique to γ-8 determined this selectivity. We also observed antagonism of AMPA receptors expressed in hippocampal, but not cerebellar, tissue from an patient with epilepsy. Corresponding to this selective activity, LY3130481 prevented multiple seizure types in rats and mice and without motor side effects. These findings demonstrate the first rationally discovered molecule targeting specific neural circuitries for therapeutic advantage.